Uterine morcellation and survival in uterine sarcomas. (September 2018) - Bretthauer, Michael; Goderstad, Jeanne Mette; Løberg, Magnus; Emilsson, Louise; Ye, Weimin; Adami, Hans-Olov; Kalager, Mette
Abstract: Background: There is concern but no solid evidence that morcellation during laparoscopic or vaginal hysterectomy may cause abdominal spread and thereby impaired prognosis of incidental uterine sarcomas. Objective: Our purpose was to compare survival among patients with uterine sarcomas who underwent hysterectomy with or without morcellation to test the hypothesis that morcellation impairs prognosis. Study design: We identified all women in Norway diagnosed with uterine sarcoma between 1953 and 2012 through national registries and retrieved data on surgical technique and morcellation by evaluation of patient files. Patients were categorised into abdominal, laparoscopic or vaginal hysterectomy with or without morcellation. Vaginal and laparoscopic hysterectomies were introduced in 1991; our main comparison is from 1991 to 2012. We compared age-adjusted disease-specific survival of sarcoma patients treated with or without morcellation and calculated age-adjusted hazard ratios (HRs) and subdistribution HR (accounting for competing risk) with 95% confidence intervals (CIs). Results: Among 1367 patients with uterine sarcoma between 1953 and 2012 in Norway, 653 were diagnosed after 1991, and 23 of these patients (3.5%) underwent morcellation. Uterine sarcoma prevalence was 3.6 per 1000 laparoscopic hysterectomies. Mean follow-up was 6.0 years in the morcellated group and 6.9 years in the non-morcellated group. The risk of dying from uterine sarcoma after morcellation was 1.5 per 1000 procedures. Sarcoma mortality was higher in the morcellated group than in the non-morcellated group (age-adjusted HR 1.90, CI 1.05–3.44; multivariate HR, 2.50, 95% CI 0.57–10.9). Age-adjusted 10-year uterine sarcoma survival was 32.2% for women treated with morcellation compared with 57.2% for non-morcellated group (difference 25.5%; CI −55.7 to 18.1). All-cause 10-year survival was 32.2% in the morcellated group and 44.1% in the non-morcellated group (difference 11.9%; CI −40.9 to 32.7). Conclusion: Our results strengthen the evidence that morcellation during hysterectomy in patients with incidental uterine sarcoma may cause impaired survival. These results can guide shared decision-making in clinical practice. Highlights: Hysterectomy with morcellation impairs prognosis in women with an undetected uterine sarcoma. The prevalence of sarcomas is low among women undergoing hysterectomy. Weighing advantages and harms of less invasive procedures requires shared decision-making.